Negative electrode material and preparation method thereof, electrochemical device and electronic device
By using porous carbon fiber skeletons and filled silicon-based materials in the negative electrode material, the problem of deterioration of electrochemical performance caused by volume expansion during charging and discharging of the silicon-based negative electrode material is solved, and the effect of improving cycling performance is achieved.
Patent Information
- Application Number
- CN202180030956.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-03-19
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-03-19
AI Technical Summary
During the charge and discharge process, silicon-based negative electrode materials will deteriorate electrochemical performance and reduce cycle stability, which limits their application due to volume expansion and the generation of unstable solid electrolyte interface films.
By preparing a negative electrode material including a porous carbon fiber skeleton and a silicon-based material filled inside it, the internal pores of the porous carbon fiber skeleton are used to alleviate volume expansion, and long-range electrical contact of the silicon-based negative electrode material is increased through the fibrous supporting framework.
It effectively alleviates the negative electrode expansion caused by the expansion of silicon-based materials and graphite, and improves the cyclic performance of the negative electrode materials.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of negative electrode materials, and in particular, to negative electrode materials and preparation methods thereof, electrochemical devices and electronic devices. Background Art
[0002] At present, silicon-based anode materials have a gram capacity of up to 1500 mAh / g to 4200 mAh / g and are considered to be the most promising next-generation lithium-ion anode materials. 8 Ω.cm), and its volume expansion of about 300% during the charge and discharge process and the generation of an unstable solid electrolyte interface film (SEI). The silicon negative electrode material will pulverize and fall from the current collector during the charge and discharge process, causing the active material to lose electrical contact with the current collector, resulting in poor electrochemical performance, capacity decay, and decreased cycle stability, which to a certain extent hinders its further application. Nano-sizing silicon-based negative electrode materials and dispersing them in a carbon matrix can effectively improve the cycle performance of silicon-based negative electrode materials. For example, silicon can be ball-milled to about 100nm by wet grinding, and then granulated with asphalt, polymers, etc. and carbonized to obtain the silicon-carbon composite material that is currently mainly used. However, the cycle performance of this negative electrode material is low and the expansion rate is relatively large. Summary of the invention
[0003] In view of this, the present application proposes a negative electrode material and a preparation method thereof, an electrochemical device and an electronic device. The negative electrode material can effectively alleviate the expansion of the negative electrode caused by the expansion of silicon base and graphite, thereby improving the cycle performance of the negative electrode material.
[0004] In a first aspect, the present application provides a negative electrode material, which includes a porous carbon fiber skeleton and a silicon-based material filled inside the porous carbon fiber skeleton; wherein the diameter of the porous carbon fiber skeleton is 0.5um to 5um, and the aspect ratio of the porous carbon fiber skeleton is 5 to 100.
[0005] In combination with the first aspect, in a feasible implementation manner, the negative electrode material further includes a carbon layer.
[0006] In combination with the first aspect, in a feasible implementation manner, the thickness of the carbon layer is 1 nm to 100 nm.
[0007] In combination with the first aspect, in a feasible implementation manner, the negative electrode material satisfies at least one of the following conditions (1) to (4):
[0008] (1) The mass percentage of silicon in the negative electrode material is 5% to 50%;
[0009] (2) The mass percentage content of carbon in the negative electrode material is 50% to 95%;
[0010] (3) The specific surface area of the negative electrode material is less than 50 m 2 / g;
[0011] (4) The powder true density of the negative electrode material is 2.0 g / cm 3 Up to 2.3g / cm 3 .
[0012] In combination with the first aspect, in a feasible embodiment, in the X-ray diffraction pattern of the negative electrode material, the highest intensity value of the diffraction peak belonging to 28.4°±0.2° is M, and the highest intensity value of the diffraction peak belonging to 45°±0.5° is N, wherein M / N≥1.
[0013] In a second aspect, an embodiment of the present application provides a method for preparing a negative electrode material, the method comprising the following steps:
[0014] The porogen and acrylonitrile are dispersed in dimethylacrylamide to form a mixed solution;
[0015] The mixed solution is prepared into polymer fibers of 0.2 um to 10 um by a spinning process;
[0016] The polymer fiber is carbonized, crushed and pickled to obtain a porous carbon fiber skeleton, wherein the diameter of the porous carbon fiber skeleton is 0.5 um to 5 um, and the aspect ratio of the porous carbon fiber skeleton is 5 to 100;
[0017] Introducing a silicon source gas into the porous carbon fiber skeleton to perform a vapor deposition to obtain a silicon-loaded carbon fiber material;
[0018] A carbon source gas is introduced into the silicon-loaded carbon fiber material to perform secondary gas phase deposition to obtain the negative electrode material.
[0019] In a third aspect, the present application provides a negative electrode plate, comprising a negative electrode current collector and a negative electrode active material layer arranged on the surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the negative electrode material described in the first aspect or the negative electrode material prepared by the negative electrode material preparation method described in the second aspect.
[0020] In a fourth aspect, the present application provides an electrochemical device, comprising a negative electrode active material layer, wherein the negative electrode active material layer comprises the negative electrode material described in the first aspect or the negative electrode material prepared by the negative electrode material preparation method described in the second aspect.
[0021] In combination with the fourth aspect, in a feasible implementation manner, the electrochemical device is a lithium-ion battery.
[0022] In a fifth aspect, the present application provides an electronic device, comprising the electrochemical device described in the fourth aspect.
[0023] Compared with the prior art, this application has at least the following beneficial effects:
[0024] The negative electrode material provided by the present application controls the size of the porous carbon fiber skeleton and the aspect ratio of the porous carbon fiber skeleton, deposits the silicon-based material into the porous carbon fiber skeleton, and utilizes the porous carbon fiber skeleton as the supporting skeleton of the negative electrode material. The internal pores of the porous carbon fiber skeleton can alleviate a certain volume expansion, and the fibrous supporting skeleton can effectively increase the long-range electrical contact of the silicon-based negative electrode material relative to the granular carbon skeleton, and can effectively alleviate the expansion of the negative electrode caused by the expansion of the silicon-based material and graphite, thereby improving the cycle performance of the negative electrode active material. DETAILED DESCRIPTION
[0025] The following is a preferred implementation of the embodiments of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the embodiments of the present application. These improvements and modifications are also considered to be within the scope of protection of the embodiments of the present application.
[0026] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.
[0027] In the description of this article, it should be noted that, unless otherwise specified, “above” and “below” are inclusive of the number itself, and “multiple” in “one or more” means more than two.
[0028] The above application content of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0029] In a first aspect, an embodiment of the present application provides a negative electrode material, which includes a porous carbon fiber skeleton and a silicon-based material filled inside the porous carbon fiber skeleton; wherein the diameter of the porous carbon fiber skeleton is 0.5um to 5um, and the aspect ratio of the porous carbon fiber skeleton is 5 to 100.
[0030] The negative electrode material provided by the present application controls the size of the porous carbon fiber skeleton and the aspect ratio of the porous carbon fiber skeleton, deposits the silicon-based material into the porous carbon fiber skeleton, and utilizes the porous carbon fiber skeleton as the supporting skeleton of the negative electrode material. The internal pores of the porous carbon fiber skeleton can alleviate a certain volume expansion, and the fibrous supporting skeleton can effectively increase the long-range electrical contact of the silicon-based negative electrode relative to the granular skeleton, and can effectively alleviate the expansion of the negative electrode caused by the expansion of the silicon-based material and graphite, thereby improving the cycle performance of the negative electrode active material.
[0031] As an optional technical solution of the present application, the diameter of the porous carbon fiber skeleton can be specifically 0.5um, 0.7um, 1.4um, 1.5um, 1.6um, 3.2um, 5.0um, etc., and of course it can also be other values within the above range, which is not limited here. The aspect ratio of the porous carbon fiber skeleton can specifically be 5, 5.5, 6.4, 6.6, 6.9, 7.0, 8.0, 12.8, 13, 20, 50 or 100, and of course it can also be other values within the above range, which is not limited here. When the diameter of the porous carbon fiber skeleton is too large, it will cause the aspect ratio to be too small, and a too small aspect ratio will cause the silicon composite material to have fewer contact sites with graphite. During the silicon expansion process, it is easy to cause the electrical contact between silicon and graphite to fail, thereby deteriorating the cycle performance of the battery cell.
[0032] As an optional technical solution of the present application, in the X-ray diffraction pattern of the negative electrode material, the maximum intensity value of the diffraction peak belonging to 28.4°±0.2° is M, and the maximum intensity value of the diffraction peak belonging to 45°±0.5° is N, wherein M / N≥1.
[0033] It should be noted that the diffraction peak attributable to 28.4° is a diffraction peak formed by silicon particles of crystalline silicon, and the diffraction peak attributable to 45° is a diffraction peak formed by carbon; the growth of the silicon peak is limited by using the carbon peak as a reference.
[0034] As an optional technical solution of the present application, the negative electrode material further includes a carbon layer, and the thickness of the carbon layer is 1nm to 100nm. It can be understood that if the carbon layer is too thick, the lithium ion transmission efficiency is reduced, which is not conducive to high-rate charge and discharge of the material and reduces the comprehensive performance of the negative electrode material. If the carbon layer is too thin, it is not conducive to increasing the conductivity of the negative electrode material and has a weak performance in inhibiting the volume expansion of the material, resulting in poor long-cycle performance.
[0035] Optionally, the thickness of the carbon layer is 1 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm or 100 nm, etc., and of course it can also be other values within the above range, which is not limited here.
[0036] As an optional technical solution of the present application, the mass percentage content of silicon in the negative electrode material is 5% to 50%; specifically, it can be 5%, 15%, 20%, 25%, 30%, 40% or 50%, etc., but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable. If the silicon content is too high, the volume expansion rate of the lithium-ion battery will increase, which is not conducive to improving the cycle stability; if the silicon content is too low, it will affect the initial efficiency and rate performance of the lithium-ion battery.
[0037] As an optional technical solution of the present application, the mass percentage content of carbon element in the negative electrode material is 50% to 95%; specifically, it can be 50%, 55%, 60%, 65%, 70%, 80% or 95%, etc., but it is not limited to the listed values, and other values not listed in the numerical range are also applicable. If the carbon content is too high, the lithium ion transmission efficiency will be reduced, which is not conducive to the high-rate charge and discharge of the material and reduces the comprehensive performance of the negative electrode material. If the carbon content is too low, it will not be conducive to increasing the conductivity of the negative electrode material and the volume expansion inhibition performance of the material is weak, resulting in a long-cycle performance price difference.
[0038] As an optional technical solution of the present application, the specific surface area of the negative electrode material is less than 50m 2 / g; specifically, it can be 1.50m 2 / g, 2.00m 2 / g, 5.0m 2 / g, 10.0m 2 / g, 15m 2 / g, 20m 2 / g, 30m 2 / g or 40m 2 / g, etc., but are not limited to the listed values, and other values not listed in the numerical range are also applicable. The specific surface area of the negative electrode material is within the above range, which ensures the processing performance of the material, is conducive to improving the initial efficiency of the lithium battery made of the negative electrode material, and is conducive to improving the cycle performance of the negative electrode material. Preferably, the specific surface area of the negative electrode material is 2.6 m 2 / g to 28 m 2 / g, further preferably, the specific surface area of the negative electrode material is 2.6 m 2 / g to 5.2 m 2 / g.
[0039] As an optional technical solution of the present application, the powder true density of the negative electrode material is 2.0 g / cm 3 Up to 2.3g / cm 3 Specific examples include 2.0 g / cm 3 , 2.05g / cm 3 , 2.1g / cm 3 , 2.15g / cm 3 , 2.2g / cm 3 , 2.25g / cm 3 or 2.3g / cm 3 , etc., but are not limited to the listed values, and other values not listed within the numerical range are also applicable. The true density of the negative electrode material is within the above range, which is beneficial to improve the energy density of the lithium battery made of the negative electrode material. The above powder true density is obtained by placing a certain mass of powder sample in a true density tester, a closed test system, introducing helium or nitrogen according to the procedure, and calculating the true volume according to Bohr's law by testing the pressure of the gas in the sample chamber and the expansion chamber.
[0040] In a second aspect, the present application provides a method for preparing a negative electrode material, the method comprising the following steps:
[0041] The porogen and acrylonitrile are dispersed in dimethylacrylamide to form a mixed solution;
[0042] The mixed solution is prepared into polymer fibers of 0.2 um to 10 um by a spinning process;
[0043] The polymer fiber is carbonized, crushed and pickled to obtain the porous carbon fiber skeleton, wherein the diameter of the porous carbon fiber skeleton is 0.5 um to 5 um, and the aspect ratio of the porous carbon fiber skeleton is 5 to 100;
[0044] A silicon source gas is introduced into the porous carbon fiber skeleton to perform a vapor deposition to obtain a silicon-loaded carbon fiber material;
[0045] A carbon source gas is introduced into the silicon-loaded carbon fiber material to perform secondary gas phase deposition to obtain the negative electrode material.
[0046] In the above scheme, silicon is deposited into a porous carbon fiber skeleton by thermal decomposition of a silicon source gas. Compared with a granular carbon skeleton, the fibrous carbon skeleton can effectively increase the long-range electrical contact of the silicon-based negative electrode material, effectively alleviate the expansion of the negative electrode caused by the expansion of the silicon base and graphite, and effectively improve the cycle performance of the negative electrode active material.
[0047] The preparation method is specifically described below in conjunction with the examples:
[0048] Step S10, dispersing the porogen and acrylonitrile in dimethylacrylamide to form a mixed solution.
[0049] In a specific embodiment, the porogen is calcium carbonate, and the particle size of the calcium carbonate particles is 10 nm to 20 nm. Specifically, it can be 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm or 20 nm, and of course, it can also be other values within the above range. By controlling the particle size of the porogen, the porogen can be adhered to the polymer fiber, and then a porous structure is formed by acid washing.
[0050] As an optional technical solution of the present application, the molecular weight of the acrylonitrile is 100w to 1000w; specifically, it can be 100w, 150w, 200w, 300w, 400w, 500w, 600w, 700w, 800w or 1000w, etc., and of course, it can also be other values within the above range.
[0051] Step S20, preparing the mixed solution into polymer fibers with a diameter of 0.2 um to 10 um through a spinning process.
[0052] As an optional technical solution of the present application, the spinning process includes at least one of electrospinning, liquid phase spinning, and melt spinning.
[0053] Step S30, carbonizing, crushing and pickling the polymer fiber to obtain the porous carbon fiber skeleton, wherein the diameter of the porous carbon fiber skeleton is 0.5um to 5um, and the aspect ratio of the porous carbon fiber skeleton is 5 to 100.
[0054] By controlling the aspect ratio of porous carbon fiber materials, the long-range electrical contact of silicon-based negative electrode materials can be effectively increased, the expansion of the negative electrode caused by the expansion of silicon-based and graphite can be effectively alleviated, and the cycle performance of the negative electrode active material can be effectively improved.
[0055] Specifically, the carbonization treatment step includes:
[0056] The polymer fiber is placed in air at 200° C. to 300° C. for oxidation for 2 h to 10 h, and then placed in an argon environment at 600° C. to 1200° C. for high-temperature carbonization for 2 h to 12 h.
[0057] During the oxidation process, acrylonitrile can undergo a cyclization reaction, which is conducive to the formation of a more stable carbon fiber material after heat treatment.
[0058] During the high-temperature carbonization process, the polymer fibers are carbonized to form carbon fibers, which can serve as the skeleton structure of the negative electrode active material and improve the cycle stability of the negative electrode active material.
[0059] As an optional technical solution of the present application, the crushing process includes at least one of ball milling, wet sand milling or high-speed airflow milling. It can be understood that the crushing process can obtain carbon fiber materials of different lengths, thereby controlling the aspect ratio of the porous carbon fiber skeleton.
[0060] As an optional technical solution of the present application, the acid solution used in the pickling treatment is hydrochloric acid or hydrofluoric acid. It can be understood that hydrochloric acid or hydrofluoric acid can react with the porogen attached to the carbon fiber, so that the porogen can be dissolved in hydrochloric acid or hydrofluoric acid, so that the carbon fiber forms a pore structure. In this embodiment, since the porogen is a nano-scale particle, the pore structure formed on the carbon fiber is also nano-scale.
[0061] Step S40, introducing a silicon source gas into the porous carbon fiber skeleton to perform a vapor deposition to obtain a silicon-loaded carbon fiber material;
[0062] It can be understood that the first vapor deposition is silicon deposition, and silicon is deposited into the carbon fiber skeleton to form nano-silicon. Since the pore structure of the carbon fiber is also nanoscale, the silicon aggregation area on the carbon fiber skeleton can be effectively controlled to be below 20nm, and the nanopore structure can also alleviate the volume expansion of silicon, thereby improving the cycle performance of silicon-based materials. In this embodiment, the silicon source gas is silane.
[0063] As an optional technical solution of the present application, the deposition temperature of the primary vapor deposition is 500°C to 900°C, specifically 500°C, 550°C, 600°C, 650°C, 700°C, 800°C or 900°C, etc., and of course it can also be other values within the above range.
[0064] As an optional technical solution of the present application, the deposition time of the primary vapor deposition is 0.25h to 24h; specifically, it can be 0.25h, 0.5h, 1h, 2h, 3h, 6h, 8h, 12h, 16h, 18h or 24h, etc., and of course, it can also be other values within the above range.
[0065] Step S50, introducing a carbon source gas into the silicon-loaded carbon fiber material to perform secondary vapor deposition to obtain the negative electrode material.
[0066] As an optional technical solution of the present application, the carbon source gas includes at least one of methane, acetylene, propane or ethylene.
[0067] As an optional technical solution of the present application, the deposition temperature of the secondary vapor deposition is 500°C to 950°C, specifically 500°C, 550°C, 600°C, 650°C, 700°C, 800°C, 900°C or 950°C, etc., and of course it can also be other values within the above range.
[0068] As an optional technical solution of the present application, the deposition time of the secondary vapor deposition is 0.5h to 12h; specifically, it can be 0.5h, 1h, 2h, 3h, 6h, 8h, 10h or 12h, etc., and of course, it can also be other values within the above range.
[0069] In a third aspect, an embodiment of the present application provides a negative electrode plate, which includes a negative electrode collector and a negative electrode active material layer located on the negative electrode collector, and the negative electrode active material layer includes the negative electrode material according to the first aspect of the present application.
[0070] As an optional technical solution of the present application, the negative electrode active material layer includes a binder, and the binder includes polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc., without limitation herein.
[0071] As an optional technical solution of the present application, the negative electrode active material layer also includes a conductive material, and the conductive material includes natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, metal powder, metal fiber, copper, nickel, aluminum, silver or polyphenylene derivatives, etc., which are not limited here.
[0072] As an optional technical solution of the present application, the negative electrode current collector includes, but is not limited to: copper foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a polymer substrate coated with a conductive metal.
[0073] In a fourth aspect, the present application further provides an electrochemical device, comprising a negative electrode active material layer, wherein the negative electrode active material layer comprises the negative electrode material described in the first aspect above or the negative electrode material prepared by the negative electrode material preparation method described in the second aspect above.
[0074] As an optional technical solution of the present application, the electrochemical device further includes a positive electrode plate, and the positive electrode plate includes a positive electrode collector and a positive electrode active material layer located on the positive electrode collector.
[0075] As an optional technical solution of the present application, the positive electrode active material includes at least one of lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material, lithium iron phosphate, lithium manganese iron phosphate, and lithium manganese oxide.
[0076] As an optional technical solution of the present application, the positive electrode active material layer further includes a binder and a conductive material. It can be understood that the binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector.
[0077] Specifically, the binder includes at least one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon.
[0078] Specifically, the conductive material includes carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0079] As an optional technical solution of the present application, the positive electrode current collector includes, but is not limited to: aluminum foil.
[0080] As an optional technical solution of the present application, the electrochemical device further includes an electrolyte, which includes an organic solvent, a lithium salt and an additive.
[0081] The organic solvent of the electrolyte according to the present application can be any organic solvent known in the prior art that can be used as a solvent for the electrolyte. The electrolyte used in the electrolyte according to the present application is not limited, and it can be any electrolyte known in the prior art. The additive of the electrolyte according to the present application can be any additive known in the prior art that can be used as an electrolyte additive.
[0082] In a specific embodiment, the organic solvent includes, but is not limited to: ethylene carbonate (EC), propylene carbonate
[0083] (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate or ethyl propionate.
[0084] In a specific embodiment, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt.
[0085] In a specific embodiment, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate
[0086] (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalatoborate) LiB(C2O4)2 (LiBOB) or lithium difluorooxalatoborate LiBF2(C2O4) (LiDFOB).
[0087] In a specific embodiment, the concentration of the lithium salt in the electrolyte may be 0.5 mol / L to 3 mol / L.
[0088] As an optional technical solution of the present application, the electrochemical device of the present application includes, but is not limited to: all kinds of primary batteries, secondary batteries, fuel cells, solar cells or capacitors.
[0089] In a specific embodiment, the electrochemical device is a lithium secondary battery, wherein the lithium secondary battery includes, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.
[0090] In a fifth aspect, an embodiment of the present application further provides an electronic device, which includes the electrochemical device described in the fourth aspect.
[0091] As an optional technical solution of the present application, the electronic device includes, but is not limited to: laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries or lithium-ion capacitors, etc.
[0092] The following takes lithium ion batteries as an example and describes the preparation of lithium ion batteries in combination with specific embodiments.
[0093] The skilled person will understand that the preparation methods described in this application are only examples, and any other suitable preparation methods are within the scope of this application.
[0094] 1. Preparation of negative electrode materials
[0095] Dispersing calcium carbonate and acrylonitrile with a particle size of 10 nm to 20 nm in dimethylacrylamide to form a mixed solution;
[0096] The mixed solution is prepared into polymer fibers of 0.2 um to 10 um by a spinning process;
[0097] The polymer fiber is placed in air at 250° C. for oxidation for 5 hours and then subjected to high-temperature carbonization, and is placed in an inert atmosphere for sintering at 1000° C. for 8 hours and then subjected to crushing and acid washing to obtain a porous carbon fiber skeleton;
[0098] Introducing silane gas into the porous carbon fiber skeleton to perform a vapor deposition, controlling the deposition temperature to be 500° C. to 900° C. and the deposition time to be 0.25 h to 24 h, to obtain a carbon fiber material loaded with silicon;
[0099] Ethylene gas is introduced into the silicon-loaded carbon fiber material to perform secondary vapor deposition, and the deposition temperature is controlled to be 500° C. to 950° C. and the deposition time is 0.5 h to 12 h to obtain the negative electrode material, wherein the thickness of the carbon layer is 1 nm to 100 nm.
[0100] Examples 1 to 9 were prepared according to the above method. The specific parameters of Examples 1 to 9 are shown in Table 1 below.
[0101] Furthermore, Comparative Example 1 was prepared according to the above method. The aspect ratio of the porous carbon fiber skeleton prepared in Comparative Example 1 was 1.0. The specific parameters of Comparative Example 1 are shown in Table 1 below.
[0102] Furthermore, according to the above method, comparative example 2 was prepared. During the preparation of comparative example 2, the mixed solution was not spun into polymer fibers, but was made into block polymers. The carbon skeleton in the prepared negative electrode material was spherical. The specific parameters of comparative example 2 are shown in Table 1 below.
[0103] Table 1. Carbon skeleton performance parameters
[0104]
[0105] 2. Performance test of negative electrode materials:
[0106] (1) Observation of the microscopic morphology of negative electrode material powder particles:
[0107] The powder microstructure was observed by scanning electron microscope to characterize the surface condition of the material. The selected testing instrument was OXFORD EDS (X-max-20mm 2 ), the accelerating voltage was 10KV, the focus was adjusted, the observation magnification was from 50K for high-magnification observation, and the low magnification of 500 to 2000 was mainly used to observe the particle agglomeration.
[0108] (2) Diameter test method of porous carbon fiber skeleton:
[0109] 20 fibers were randomly selected using SEM, and the diameter and length of the fibers were tested to obtain the diameter and length of each fiber. The fiber diameter was averaged to obtain the fiber diameter, and the fiber length was averaged to obtain the fiber length. The two were compared to obtain the aspect ratio of the fiber.
[0110] (3) Test method for silicon content in negative electrode materials:
[0111] Weigh 0.05 to 0.1 g of sample, add 1.2 to 1.5 g of dry potassium hydroxide, put it into a muffle furnace at 400°C, cool it, add boiling water to soak it, wash it repeatedly, filter the sample solution into a 100 mL PP bottle with medium-speed filter paper and make up the volume, then dilute it 100 times, use ICP-OES to test the dilution, and then calculate the silicon content of the sample.
[0112] (4) Test method for specific surface area of negative electrode material:
[0113] At constant temperature and low temperature, after measuring the adsorption amount of gas on the solid surface at different relative pressures, the monolayer adsorption amount of the sample is obtained based on the Brownauer-Etter-Taylor adsorption theory and its formula (BET formula), thereby calculating the specific surface area of the solid.
[0114] About 1.5 g to 3.5 g of powder sample was weighed and placed into the test sample tube of TriStar II 3020, and the test was performed after degassing at about 200° C. for 120 min.
[0115] (5) Test method for true density of negative electrode material:
[0116] Weigh a certain mass of sample (1g to 5g), place it in the true density tester, close the test system, and introduce helium or nitrogen according to the procedure. By testing the pressure of the gas in the sample chamber and the expansion chamber, the real volume is calculated according to Bohr's law (PV=nRT), and then the true density is calculated.
[0117] (6) Testing method for carbon content in negative electrode materials:
[0118] The sample is heated and burned at high temperature in a high-frequency furnace under oxygen-rich conditions to oxidize carbon and sulfur into carbon dioxide and sulfur dioxide. After treatment, the gas enters the corresponding absorption cell, absorbs the corresponding infrared radiation, and then is converted into a corresponding signal by the detector. This signal is sampled by a computer, converted into a value proportional to the concentration of carbon dioxide and sulfur dioxide after linear correction, and then the values of the entire analysis process are accumulated. After the analysis is completed, this accumulated value is divided by the weight value in the computer, multiplied by the correction coefficient, and the blank is deducted to obtain the percentage of carbon and sulfur in the sample. The sample is tested using a high-frequency infrared carbon and sulfur analyzer (Shanghai Dekai HCS-140).
[0119] (7) X-ray diffraction test of negative electrode materials:
[0120] 1.0 g to 2.0 g of the sample was weighed and poured into the groove of the glass sample holder, and it was compacted and smoothed with a glass sheet. An X-ray diffractometer (Bruker, D8) was used for testing in accordance with JJS K 0131-1996 "General Rules for X-ray Diffraction Analysis". The test voltage was set to 40 kV, the current was 30 mA, the scanning angle range was 10° to 85°, the scanning step was 0.0167°, and the time set for each step was 0.24 s. The XRD diffraction pattern of the negative electrode material was obtained, and the highest intensity value M at 2θ belonging to 28.4° and the highest intensity value N at 45° were obtained from the XRD diffraction pattern, thereby calculating the ratio of M / N.
[0121] 3. Preparation of lithium batteries
[0122] (1) Preparation of positive electrode
[0123] The positive electrode active material lithium cobalt oxide (LiCoO2), conductive carbon black, and binder polyvinylidene fluoride are mixed in a weight ratio of 95:2.5:2.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil; the aluminum foil is dried, and then cold pressed, cut, and slit, and then dried under vacuum conditions to obtain a positive electrode sheet.
[0124] (2) Preparation of negative electrode
[0125] The negative electrode materials, graphite, conductive agent (conductive carbon black, Super P®) and binder PAA of the above embodiments and comparative examples were mixed in a weight ratio of 70:15:5:10, deionized water was added, and negative electrode slurry was obtained under the action of a vacuum mixer; the negative electrode slurry was evenly coated on the negative electrode current collector copper foil; the copper foil was dried, and then cold pressed, cut into pieces, and slit, and then dried under vacuum conditions to obtain a negative electrode sheet.
[0126] (3) Electrolyte
[0127] In a dry argon atmosphere glove box, LiPF6 was added to a solvent mixed with propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) (weight ratio of about 1:1:1), wherein the concentration of LiPF6 was about 1.15 mol / L, and the mixture was evenly mixed to obtain an electrolyte.
[0128] (4) Isolation film
[0129] A polyethylene porous polymer film is used as the isolation membrane.
[0130] (5) Preparation of lithium-ion batteries
[0131] The positive electrode, the separator and the negative electrode are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain a bare cell; after welding the pole ears, the bare cell is placed in an outer packaging foil aluminum-plastic film, and the prepared electrolyte is injected into the dried bare cell. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, a lithium-ion battery is obtained.
[0132] 4. Performance test of lithium battery:
[0133] (1) Lithium-ion battery cycle performance test
[0134] Place the lithium-ion battery in a 45℃ (25℃) thermostat and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at a constant current of 0.7C to a voltage of 4.4V, then charge it at a constant voltage of 4.4V to a current of 0.025C, let it stand for 5 minutes, and discharge it at a constant current of 0.5C to a voltage of 3.0V. The capacity obtained in this step is taken as the initial capacity, and a cycle test is performed at 0.7C charging / 0.5C discharging. The capacity at each step is compared with the initial capacity to obtain a capacity decay curve. The number of cycles at 25℃ until the capacity retention rate is 90% is recorded as the room temperature cycle performance of the battery, and the number of cycles at 45℃ until the capacity retention rate is 80% is recorded as the high temperature cycle performance of the battery. The cycle performance of the material is compared by comparing the number of cycles in the above two cases.
[0135] (2) Discharge rate test:
[0136] The lithium-ion battery was placed in a 25°C thermostat and allowed to stand for 30 minutes to reach a constant temperature. The lithium-ion battery that reached a constant temperature was discharged at a constant current of 0.2C to a voltage of 3.0V, allowed to stand for 5 minutes, charged at a constant current of 0.5C to a voltage of 4.45V, then charged at a constant voltage of 4.45V to a current of 0.05C and allowed to stand for 5 minutes, the discharge rate was adjusted, and the discharge test was performed at 0.2C, 0.5C, 1C, 1.5C, and 2.0C, respectively, to obtain the discharge capacity, and the capacity obtained at each rate was compared with the capacity obtained at 0.2C, and the rate performance was compared by comparing the ratios at 2C and 0.2C.
[0137] (3) Battery full charge expansion rate test:
[0138] Use a screw micrometer to test the thickness of a fresh battery at half charge (50% state of charge (SOC)). When the battery is fully charged (100% SOC) after 400 cycles, use a screw micrometer to test the thickness of the battery at this time. By comparing it with the thickness of the fresh battery at the initial half charge (50% SOC), the expansion rate of the fully charged (100% SOC) battery can be obtained.
[0139] The performance parameters of the negative electrode materials of Examples 1 to 3 and the negative electrode material of Comparative Example 1 prepared according to the above method are shown in Table 1-1, and the performance test results of the lithium batteries prepared therefrom are shown in Table 1-2.
[0140] Table 1-1
[0141]
[0142] It should be noted that the gram capacity in this application form is the gram capacity with a discharge cut-off voltage of 2.0V;
[0143] The initial efficiency calculation method in this application form is the capacity at a discharge end voltage of 2.0V / the capacity corresponding to a charge end voltage of 0.005V.
[0144] Table 1-2
[0145]
[0146] It can be seen from the test results of Examples 1 to 3 that when the same type of carbon fiber skeleton is used, as the silicon content deposited on the carbon fiber skeleton increases, the gram capacity of the negative electrode materials of Examples 1 to 3 gradually increases, and the first efficiency of the battery is also improved. However, the cycle performance of the battery decreases with the increase of silicon content, and the battery expansion rate also increases; it can be seen that the silicon content of the negative electrode material needs to be controlled. Preferably, the mass percentage content of silicon in the negative electrode material is 17.2% to 39%.
[0147] In Comparative Example 1, spherical carbon skeleton particles are used, and the cycle performance of the lithium battery is significantly reduced and the expansion efficiency is significantly increased compared with Examples 1 to 3. This is because the carbon fiber skeleton can effectively increase the long-range electrical contact of the negative electrode material compared with the spherical carbon skeleton particles, and can alleviate the expansion of the negative electrode caused by silicon and graphite, thereby improving the cycle performance of the negative electrode material.
[0148] The performance parameters of the negative electrode materials of Examples 4 to 6 and the negative electrode material of Comparative Example 1 prepared according to the above method are shown in Table 2-1, and the performance test results of the lithium batteries prepared therefrom are shown in Table 2-2.
[0149] Table 2-1
[0150]
[0151] Table 2-2
[0152]
[0153] From the test results of Examples 4 to 6, it can be seen that the diameter of the porous carbon fiber skeleton used in Example 4 is 1.5um, the diameter of the porous carbon fiber skeleton used in Example 5 is 3.2um, and the diameter of the porous carbon fiber skeleton used in Example 6 is 5.1um, and the aspect ratio of the porous carbon fiber skeletons of Examples 4 to 6 is in the range of 5.4 to 6.9, and the silicon content and carbon content of the negative electrode material are similar. It can be seen that when the diameter of the porous carbon fiber skeleton is greater than 5um, the cyclability of the lithium-ion battery will decrease instead. Therefore, the diameter of the porous carbon fiber skeleton should be controlled to be 0.5um to 5um.
[0154] The performance parameters of the negative electrode materials of Examples 7 to 9 and the negative electrode material of Comparative Example 2 prepared according to the above method are shown in Table 3-1, and the performance test results of the lithium batteries prepared therefrom are shown in Table 3-2.
[0155] Table 3-1
[0156] sample Carbon skeleton type Silicon content (%) Carbon content (%) <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[True density (g.cm 3 )]]> M / N Gram capacity (mAh / g) First effect (%) Example 7 Carbon fiber frame 4 35 58.6% 3.4 2.15 12.8 1126 79.9 Example 8 Carbon fiber skeleton 2 37 56.8 5.2 2.23 7.0 1177 82.7 Example 9 Carbon fiber frame 5 33 60.4 4.5 2.21 6.4 1074 79.3 Comparative Example 2 Comparison of carbon skeleton 1 24.9 68.5 4.6 2.17 / 856 77.4
[0157] Table 3-2
[0158] sample 25℃ cycle until 90% of the number of cycles Battery expansion rate after 400 cycles at 25℃ 45℃ cycle until 90% of the number of cycles Battery expansion rate after 400 cycles at 45°C Example 7 490 5.2% 450 5.9% Example 8 480 5.4% 440 6.0% Example 9 450 5.6% 420 6.2% Comparative Example 2 420 6.2% 370 6.8 %
[0159] It can be seen from the test results of Examples 7 to 9 that when the diameter of the porous carbon fiber skeleton is 0.5um to 5um, and the aspect ratio of the porous carbon fiber skeleton is 5 to 100, the lithium ion battery has good cycle performance and rate performance, and a lower expansion rate. When the carbon fiber skeleton is used in Comparative Example 2, and its aspect ratio is less than 5, the cycle performance and rate performance of the lithium ion battery are poor, and the expansion rate is high.
[0160] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.
Claims
1. A negative electrode material, characterized in that: The negative electrode material comprises a porous carbon fiber skeleton and a silicon-based material filled inside the porous carbon fiber skeleton; wherein the diameter of the porous carbon fiber skeleton is 0.5 um to 5 um, and the aspect ratio of the porous carbon fiber skeleton is 5 to 100; In the X-ray diffraction spectrum of the negative electrode material, the maximum intensity value of the diffraction peak belonging to 28.4°±0.2° is M, and the maximum intensity value of the diffraction peak belonging to 45°±0.5° is N, wherein M / N≥1.
2. The negative electrode material according to claim 1, characterized in that The negative electrode material further comprises a carbon layer.
3. The negative electrode material according to claim 2, characterized in that The carbon layer has a thickness of 1 nm to 100 nm.
4. The negative electrode material according to claim 1, characterized in that The negative electrode material satisfies at least one of the following conditions (1) to (4): (1) The mass percentage content of silicon in the negative electrode material is 5% to 50%; (2) The mass percentage content of carbon element in the negative electrode material is 50% to 95%; (3) The specific surface area of the negative electrode material is less than 50 m 2 / g; (4) The powder true density of the negative electrode material is 2.0 g / cm 3 Up to 2.3g / cm 3 .
5. A method for preparing a negative electrode material as claimed in claim 1 or 2, characterized in that: The method comprises the following steps: Dispersing a porogen and acrylonitrile in dimethyl acrylamide to form a mixed solution, wherein the porogen is calcium carbonate particles, and the particle size of the calcium carbonate particles is 10 nm to 20 nm; The mixed solution is prepared into polymer fibers of 0.2 um to 10 um by a spinning process; The polymer fiber is carbonized, crushed and pickled to obtain a porous carbon fiber skeleton, wherein the diameter of the porous carbon fiber skeleton is 0.5 um to 5 um, and the aspect ratio of the porous carbon fiber skeleton is 5 to 100; Introducing a silicon source gas into the porous carbon fiber skeleton to perform a vapor deposition to obtain a silicon-loaded carbon fiber material; A carbon source gas is introduced into the silicon-loaded carbon fiber material to perform secondary gas phase deposition to obtain the negative electrode material.
6. The preparation method according to claim 5, characterized in that: The negative electrode material satisfies at least one of the following conditions (1) to (5): (1) The mass percentage content of silicon in the negative electrode material is 5% to 50%; (2) The mass percentage content of carbon element in the negative electrode material is 50% to 95%; (3) The specific surface area of the negative electrode material is less than 50 m 2 / g; (4) The powder true density of the negative electrode material is 2.0 g / cm 3 Up to 2.3g / cm 3 ; (5) The thickness of the carbon layer of the negative electrode material is 1 nm to 100 nm.
7. The preparation method according to claim 5, characterized in that: The method satisfies at least one of the following conditions (6) to (7): (6) The deposition temperature of the primary vapor deposition is 500°C to 900°C, and the deposition time is 0.25h to 24h; (7) The silicon source gas is silane.
8. The preparation method according to claim 5, characterized in that: The method satisfies at least one of the following conditions (8) to (9): (8) The deposition temperature of the secondary vapor deposition is 500°C to 950°C, and the deposition time is 0.5h to 12h; (9) The carbon source gas includes at least one of methane, acetylene, propane or ethylene.
9. The preparation method according to claim 5, characterized in that: The method satisfies at least one of the following conditions (10) to (12): (10) The carbonization treatment conditions include oxidizing the polymer fiber in air at 200° C. to 300° C. for 2 h to 10 h, and then subjecting the polymer fiber to high-temperature carbonization at 600° C. to 1200° C. for 2 h to 12 h; (11) The crushing process includes at least one of ball milling, wet sand milling or high-speed airflow milling; (12) The acid solution used in the pickling treatment is hydrochloric acid or hydrofluoric acid.
10. The preparation method according to claim 5, characterized in that: The method satisfies at least one of the following conditions (13) to (14): (13) The molecular weight of the acrylonitrile is 100w to 1000w; (14) The spinning process includes at least one of electrospinning, liquid phase spinning, and melt spinning.
11. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, characterized in that: The negative electrode active material layer comprises the negative electrode material according to any one of claims 1 to 4 or the negative electrode material prepared by the negative electrode material preparation method according to any one of claims 5 to 10.
12. An electrochemical device comprising a negative electrode active material layer, characterized in that: The negative electrode active material layer comprises the negative electrode material according to any one of claims 1 to 4 or the negative electrode material prepared by the negative electrode material preparation method according to any one of claims 5 to 10.
13. The electrochemical device according to claim 12, characterized in that The electrochemical device is a lithium ion battery.
14. An electronic device, characterized in that: The electronic device comprises the electrochemical device according to claim 12.
Citation Information
Patent Citations
Silicon-based negative electrode material and preparation method thereof
CN105118974A